Imputing consumption from Norwegian income and wealth registry data - Andreas Fagereng; Elin Halvorsen (Statistics Norway, Research Department, 2015)
Data on consumption expenditure of the household is essential in a wide array of economic research. This includes both topics in micro as well as macroeconomics. However, obtaining a consistent and precise measure of household consumption has proven notoriously difficult. This paper documents a method for computing a longitudinal consumption measure for Norwegian households from administrative records of income and wealth. Expenditure surveys tend to suffer from limited sample sizes and underrepresentation of high-income households. Administrative data does not have such limitations and offers a much larger sample with better coverage of all household types. This is particularly useful for improving the measurement of heterogeneity in consumption behavior.
Keywords: D12; D14; D31; E21; G11; 330; consumption measurement; savings; household finance